2014
DOI: 10.1007/s10943-014-9908-1
|View full text |Cite
|
Sign up to set email alerts
|

Religious Orientation, Endorser Credibility, and the Portrayal of Female Nurses by the Media

Abstract: Medical consumption and media culture in Taiwan contain clear religious elements. It is common for people to believe that medicine is a supernatural treatment and to rely on thoughts of unseen power instead of rational consciousness. Religious-influenced patriarchy, seen in cultural gender roles, significantly influences religious adherents and degrades women as being part of a secondary class in society. As a contradictory tradition, women, in comparison to men, are considered best at undertaking certain jobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Religious orientation is a common strategy used by researchers to study the influence of religion on individual (Meagher, 2018) as it indicates the desire or sensitivity of a person towards religious advancement. Past literature on religious orientation has shown its significant impact in influencing consumers’ decision-making (Lin et al , 2015; Moltafet et al , 2010; Steffen et al , 2015). Contrary to the past literature, our research showed an insignificant impact of religious orientation on both actual purchase behaviour and repurchase intention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious orientation is a common strategy used by researchers to study the influence of religion on individual (Meagher, 2018) as it indicates the desire or sensitivity of a person towards religious advancement. Past literature on religious orientation has shown its significant impact in influencing consumers’ decision-making (Lin et al , 2015; Moltafet et al , 2010; Steffen et al , 2015). Contrary to the past literature, our research showed an insignificant impact of religious orientation on both actual purchase behaviour and repurchase intention.…”
Section: Discussionmentioning
confidence: 99%
“…For a competitive and effective strategic marketing, examining the behaviour of consumers is very crucial, as it allows companies to identify and anticipate how consumers would behave (Schiffman and Kanuk, 2004). As consumers after-sales experience furnishes collective vibe that causes consumers to buy the product again (Lin et al , 2015), it is essential for marketers to learn how Indian Muslim consumers respond to the concept of halal consumption, what determines their actual purchase behaviour and what can shape their repurchase intentions.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…The first drawback could be the example of a local parent, which might lead to a mono‐operational bias: a single local parent's appearance speaking with a local accent might be less attractive for young urban consumers from different cultures. Endorsers' or spokespeople's attractive and professional appearance can produce a better advertising effect (Lin et al., 2014). Words from the mouth of attractive endorsers are believed to be more convincing than those from less attractive ones (Chaiken, 1979).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…Access can also be restricted through ability or beliefs. Illiteracy, religious views, and stereotypes may hinder the adoption of products and services (Lin et al, 2015). Access can also be shaped by gender, as women represent a disproportionate percentage of people living in poverty (Chant, 2006).…”
Section: Building An Integrated Model Of Resource Scarcitymentioning
confidence: 99%